The European Union and China, 1949-2008 [ basic documents and commentary - Snyder, Francis G. (China and international economic law series, 2009)
A comprehensive reference book and commentary on basic documents about relations between the EU and the People's Republic of China from 1949 onwards. It contains various significant official and unofficial documents in English and Chinese about EU-China relations since the founding of the PRC in 1949